Sustainable development in Cuba assessed with sustainability window and doughnut economy approaches - Saunders Anaely; Luukkanen Jyrki (Taylor & Francis, 2022)
Sustainability Window (SuWi) analysis is a novel tool to analyze the minimum economic development to fulfill the requirements for social sustainability and the maximum economic development not to surpass the environmental limits. The method provides quantitative measures to define whether the real development of GDP is within the sustainability limits using different indicators for measuring social welfare and environmental stress. The SuWi results can be used to form a visualization of the sustainability doughnut to illustrate the critical areas of development where policy intervention may be needed to reach sustainability. The doughnut economy visualization is constructed for Cuban development for the analysis of both strong and weak sustainability.